CASE STUDY OF LIBRARY MANAGEMENT IN SD INPRES 2 MENSUNG, PARIGI MOUTONG - Rusmawati Rahim (Jurnal Madako Education, 2020)
Teachers Training and Education faculty Madako University. Realized to imported of imformation that on the library to using, there for librarian or organized must to appropriated served with the purpose and library fungtion have diceded. Then, librarian must teaching and aims to library visitor in searching the books materials to need. On The other hand, this research to purpose for knows how to librarian served. Infraastructure, organized and preservation books materials in the librarian SD Inp 2 Mensung This research is descriptive research observation, interview and documentation used in data collected, and the total subject is 3 people’s. There are head of librarian and 2 students, based on criterian students that choos which had permanent by the researcher that is the students can give accurated information. The result of this research sumarize that librarian played in give the saved to librarian visitor as maksima, but will in matthen suply the material books and aad book collection by librarian did steel less.